2014
DOI: 10.1007/s00779-014-0759-2
|View full text |Cite
|
Sign up to set email alerts
|

User interaction with everyday lighting systems

Abstract: New lighting technologies create new opportunities that may contribute to people's experience of light. These opportunities are a result of the increased variety and freedom in terms of colour, form factor and connectivity of the lights. To allow people to fully benefit from the potential of such novel lighting systems, there is a need for a new user interaction paradigm. To develop this paradigm, we have to better understand the aspects that play a part in the interaction with lighting, paying special attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 26 publications
3
27
0
Order By: Relevance
“…Also, because of the designed triggers, people interacted even less with the light to avoid possible conflicts or undesired influence on others. This was also found by Offermans et al [23]. The interpersonal conflicts, even though small in number, matched the conflict types of the previous study: we observed a preference, an activity, and an attitude conflict.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Also, because of the designed triggers, people interacted even less with the light to avoid possible conflicts or undesired influence on others. This was also found by Offermans et al [23]. The interpersonal conflicts, even though small in number, matched the conflict types of the previous study: we observed a preference, an activity, and an attitude conflict.…”
Section: Discussionsupporting
confidence: 92%
“…A perceived conflict is noticed by some or all parties but is not explicated like a manifest conflict is [10]. We expect, based on the findings by Offermans et al [23], that in lighting many conflicts remain latent. Interestingly, Deutsch found that conflict is not necessarily negative: conflict can be productive in the sense that it can stimulate curiosity, prevents stagnation, and leads to social change [29].…”
Section: Conflicts and Conflict Resolutionmentioning
confidence: 86%
See 3 more Smart Citations